(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The pancreas has important exocrine and endocrine functions, producing hormones (insulin, glucagon, somatostatin, and pancreatic polypeptide) and a number of extremely powerful digestive enzymes. Therefore, diseases of the pancreas have a significant impact on the body as a whole, resulting in severe complications and a high mortality rate. At the same time, diagnostics are not always successful, which is partly due to the retroperitoneal location of this organ and the vagueness of clinical and biochemical symptoms